THE INFLUENCE OF CORDIERITE ON MELTING AND MINERAL-MELT EQUILIBRIA IN ULTRA-HIGH-TEMPERATURE METAMORPHISM - Harley S.L.; Thompson P. (My University, 2004)
Experimentally constrained calibrations of the incorporation of H2O and CO2 into cordierite as functions of P-T-a(H2O)-a(CO2) are integrated with KFMASH grids which define mineral-melt equilibria in pelites. This is used to explore the impact of the volatile content and composition of cordierite on anatexis and melt-related processes in high-temperature (HT) and ultra-high-temperature (UHT) metamorphism. The strongly temperature-sensitive H2O content of cordierite coexisting with dehydration melts (0.4-1.6 wt.%) causes a 10-25% relative decrease in the amount of melt produced from pelites compared with models which treat cordierite as anhydrous. KFMASH melting grids quantified for a(H2O) demonstrate consistency between the measured H2O contents in cordierite from granulite-migmatite terrains and mineral equilibria. These indicate anatexis with a(H2O) in the range 0.26-0.16 at 6-8 kbar and 870-930 degrees C. The pressure-stability of cordierite + garnet with respect to orthopyroxene + sillimanite + quartz in KFMASH is strongly influenced by cordierite H2O content, which decreases from 1.1 to 0.5wt.% along the melting reaction Grt + Crd(H) + Kfs = Opx + Sil + Qz + L. The lower-T invariant point involving biotite (8.8kbar/900 degrees C) that terminates this reaction has a(H2O) of 0.16 +/- 0.03, whereas the higher-T terminating invariant point involving osumilite (7.90bar/940 degrees C) occurs at a(H2O) 0.08 +/- 0.02. Osumilite-bearing assemblages in UHT terrains imply a(H2O) of < 0.08, and at 950-1000 degrees C and 8-9 kbar calculated a(H2O) is only 0.04-0.02. Cordierites stable in osumilite-bearing assemblages or with sapphirine + quartz have maximum predicted H2O contents of ca. 0.2 wt.%, consistent with H2O measured in cordierites from two sapphirine-bearing UHT samples from the Napier Complex. The addition of CO2 to the H2O-undersaturated (dehydration-melting) system marginally decreases the temperature of melting because of the stabilisation of cordierite, the solid product of the peritectic melting reactions. The preferential incorporation of CO2 enhances the stability of cordierite, even at fixed a(H2O) and causes the stability fields of Grt + Crd + Sil + Kfs + Qz + L and Grt + Opx + Crd + Kfs + Qz + L to expand to higher pressure, and to both higher and lower temperatures. The minimum solubility of H2O in granitic melt is independent of the CO2 content of cordierite, and the distribution of H2O between melt and cordierite is similar at a given melt H2O-content to the H2O-only system. This enhanced stability of CO2-bearing cordierite leads to a reduced stability range for osumilite-bearing assemblages to temperatures of ca. 950-975 degrees C or greater. Cordierites in the Napier Complex UHT gneisses contain 0.5 and 1.05 wt.% CO2, consistent with a role for CO2 in stabilising cordierite with respect to osumilite in these unusual sapphirine-bearing granulites.
Keywords: Fluids; granites; granulites; osumilite; sapphirine